Resurgence of pertussis at the age of vaccination: clinical, epidemiological, and molecular aspects - Rosângela S.L.A. Torres; Talita Z. Santos; Robson A.A. Torres; Valéria V.G. Pereira; Lucas A.F. Fávero; Otavio R.M. Filho; Margareth L. Penkal; Leni S. Araujo (Elsevier, 2015)
Objective: Report the incidence, epidemiology, clinical features, death, and vaccination status of patients with whooping cough and perform genotypic characterization of isolates of B. pertussis identified in the state of Paraná, during January 2007 to December 2013. Methods: Cross-sectional study including 1,209 patients with pertussis. Data were obtained through the Notifiable Diseases Information System (Sistema de Informação de Agravos de Notificação - SINAN) and molecular epidemiology was performed by repetitive sequence-based polymerase chain reaction (rep-PCR; DiversiLab®, bioMerieux, France). Results: The incidence of pertussis in the state of Paraná increased sharply from 0.15-0.76 per 100,000 habitants between 2007-2010 to 1.7-4.28 per 100,000 between 2011-2013. Patients with less than 1 year of age were more stricken (67.5%). Fifty-nine children (5%) developed pertussis even after receiving three doses and two diphtheria-tetanus-pertussis (DTP) boosters vaccine. The most common complications were pneumonia (14.5%), otitis (0.9%), and encephalopathy (0.7%). Isolates of B. pertussis were grouped into two groups (G1 and G2) and eight distinct patterns (G1: P1-P5 and G2: P6-P8). Conclusion: The resurgence of pertussis should stimulate new research to develop vaccines with greater capacity of protection against current clones and also encourage implementation of new strategies for vaccination in order to reduce the risk of disease in infants. Resumo: Objetivo: Relatar a incidência, aspectos epidemiológicos, clínicos, morte e a vacinação de pacientes com coqueluche e realizar a caracterização genotípica de isolados de B. pertussis identificados no estado do Paraná, de janeiro de 2007 a dezembro de 2013. Métodos: Estudo transversal, incluindo 1.209 pacientes com coqueluche. Os dados foram obtidos através do Sistema de Informação de Agravos de Notificação (SINAN) e a epidemiologia molecular foi realizada por PCR baseada em sequências repetitivas (rep-PCR; DiversiLab®, bioMerieux, France). Resultados: A incidência de coqueluche no Estado do Paraná aumentou acentuadamente de 0,15-0,76 por 100.000 habitantes entre 2007-2010 para 1,7-4,28 por 100.000 habitantes entre 2011-2013. Os pacientes com menos de um ano de idade foram os mais afetados (67,5%). Cinquenta e nove crianças (5%) desenvolveram coqueluche mesmo depois de receber três doses da vacina e dois reforços com a vacina tríplice DTP. As complicações mais comuns foram pneumonia (14,5%), otite (0,9%) e encefalopatia (0,7%). Isolados de B. pertussis foram agrupados em dois grupos (G1 e G2) e oito padrões distintos (G1: P1-P5 e G2: P6-P8). Conclusão: O ressurgimento da coqueluche vem para sugerir novas pesquisas com o objetivo se desenvolver vacinas com maior capacidade de proteção contra os clones atuais e também implementar novas estratégias de vacinação, a fim de reduzir o risco de doenças em lactentes. Keywords: Whooping cough, Clones, Bordetella pertussis, Rep-PCR, Vaccine, Incidence, Palavras-chave: Coqueluche, Clones, Bordetella pertussis, Rep-PCR, Vacinas, Incidência